HUBUNGAN TINGKAT PENDIDIKAN, PENGETAHUAN DAN SIKAP DENGAN PERILAKU PENGELOLAAN SAMPAH PADA PEDAGANG BUAH DAN SAYUR DI PASAR GIWANGAN YOGYAKARTA - Ahmad Faizal Rangkuti; May Erviana Safitri (Jurnal Kesehatan dan Pengelolaan Lingkungan, 2022)
Waste management is a waste storage, collection and eradication activity carried out in such a way that waste does not interfere with public health and the environment. Poor waste management will have a negative impact on the surrounding environment. The negative impacts include flooding, slums and causing several diseases such as dysentery, cholera, asciariasis. The results of previous studies revealed that waste management in Giwangan Market has not been in accordance with the standards. Previous research concluded that waste management behavior is influenced by the level of education, knowledge and attitudes. The purpose of this study was to determine the relationship of education level, knowledge and attitudes with waste management behavior in fruit and vegetable traders in Giwangan Market, Yogyakarta. This type of research is a quantitive study using observasional analytic methods and cross sectional design. The research sample uses a simple random sampling of 171 fruits and vegetables traders. The research instrument used questionnaires. Data analysis used univariate and bivariate analysis with chi square statictical test. The results showed that respondents with low education level as many as 122 (71,3%), not good knowledge as many as 86 (50,3%), not good attitude as many as 99 (57,9%) and not good behavior as many as 113 (66,1%) respondents. Statistical results showed there was a correlation of level education (p value=0,036), knowledge (p value=0,018) and attitude (p value=0,003) with behavior of waste management. There was correlation between level of education, knowledge and attitude with behavior of waste management in fruits and vegetables traders on the Giwangan Market Yogyakarta.